PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Basuki . Basuki; Rahmi Widyanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
Objective this research is to examine and analyze the influence of tranformational leadership, job motivation and discipline toward performance of employee in PT. Karya Mandiri Distric Kalimantan. Data collected through distribution of questionnaires, and it is implemented to PT. Karya Mandiri Distric Kalimantan 108 employee. Analysis of data in this research using the help of SPSS version 27. A sampling technique uses a census method and data test technique is used within the research includes validity test by factor analysis, reliability test with cronbach.Analysis result demonstrates that transformational leadership have a positive influence toward employee performance. Job motivation has a positive influence toward employee performance and job discipline have a positive influence toward employee performance.